2008
DOI: 10.1093/nar/gkn423
|View full text |Cite
|
Sign up to set email alerts
|

Rational vector design and multi-pathway modulation of HEK 293E cells yield recombinant antibody titers exceeding 1 g/l by transient transfection under serum-free conditions

Abstract: Transient transfection allows for fast production of recombinant proteins. However, the current bottlenecks in transient transfection are low titers and low specific productivity compared to stable cell lines. Here, we report an improved transient transfection protocol that yields titers exceeding 1 g/l in HEK293E cells. This was achieved by combining a new highly efficient polyethyleneimine (PEI)-based transfection protocol, optimized gene expression vectors, use of cell cycle regulators p18 and p21, acidic F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
164
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(166 citation statements)
references
References 21 publications
2
164
0
Order By: Relevance
“…Our SINEUP system adds to those already established for optimization of mAb production. 11-13 The combination of SINEUP technology with existing and upcoming technologies will be evaluated in the future, to verify whether optimal mAb production can be reached, in terms of even more pronounced yields and unaltered PTMs.…”
Section: Resultsmentioning
confidence: 99%
“…Our SINEUP system adds to those already established for optimization of mAb production. 11-13 The combination of SINEUP technology with existing and upcoming technologies will be evaluated in the future, to verify whether optimal mAb production can be reached, in terms of even more pronounced yields and unaltered PTMs.…”
Section: Resultsmentioning
confidence: 99%
“…The same three expression vectors were then used to determine the effect of temperatures other than 31°C on TGE. Cells were transfected as described above and shifted to 29,31, or 33°C at 4 h post-transfection. At all three temperatures tested, there was enhancement of antibody and GFP production relative to the control culture at 37°C, with the highest yields of GFP ( Figure 2A) and antibody ( Figure 2B) at 31 and 33°C, respectively.…”
Section: Transient Gene Expression Under Mild Hypothermicmentioning
confidence: 99%
“…However, studies testing serum versus serum-free media have shown that higher titers could be obtained in serum-containing media (Durocher et al 2002), which suggests that there may be components in serum-free media that inhibit PEI-mediated transient transfection or that serum-free media lacks components necessary for successful transfections. Despite this observation, there have been reports of serum-free medium used with both 293 and CHO cells that allow levels of recombinant protein expression in the range of hundreds of milligrams per liter, with a recent study reporting over 1 g/L of recombinant monoclonal antibody produced in 293 cells (Backliwal et al 2008). In this study, we have examined several different media for their compatibility with PEI-mediated transient transfection in CHO cells.…”
Section: Introductionmentioning
confidence: 99%